Maghemite nanoparticles coated with human serum albumin: combining targeting by the iron-acquisition pathway and potential in photothermal therapies. Issue 17 (11th April 2017) - Hai, J.; Piraux, H.; Mazarío, E.; Volatron, J.; Ha-Duong, N. T.; Decorse, P.; Lomas, J. S.; Verbeke, P.; Ammar, S.; Wilhelm, C.; El Hage Chahine, J.-M.; Hémadi, M.
Abstract : Human serum albumin (HSA), the most abundant plasma protein in human blood, is a natural transport vehicle with multiple ligand binding sites. Abstract : Human serum albumin (HSA), the most abundant plasma protein in human blood, is a natural transport vehicle with multiple ligand binding sites. It, therefore, constitutes an attractive candidate for drug delivery. Targeting may occur via the most known interaction of the protein with the neonatal Fc receptor (FcRn). Here, we investigate another HSA delivery path, involving the transferrin receptor, and we elaborate a maghemite–HSA nanohybrid, opening up new opportunities for medical applications. Fluorescence spectrophotometric titration and size-exclusion chromatography were used to substantiate, in cell-free assays, an interaction between HSA and the transferrin receptor R1. This occurs with a dissociation constant, K D of 6.7 nM. This interaction was confirmed in HeLa cell culture where, by confocal microscopy, rhodamine-labeled HSA is shown to be internalized. HSA was then covalently conjugated onto maghemite nanoparticles (NPs) to give a NP–HSA nanohybrid. The therapeutic potential of this hybrid was demonstrated through its heating capacity in magnetic hyperthermia (MH) and near-infrared (NIR) photothermia (PT). In particular, the Specific Absorption Rate (SAR) in the PT Therapy (PTT) mode, using a 808 nm NIR-LASER (1 W cm −2 ) and at iron concentration as low as 2.5 mM, was found to be very high, equal to 1870 W g −1 with a temperature increment of 9.2 °C. The nanohybrids incubated with HeLa cells were mainly localized at the cell surface. When the PTT mode was applied under the same conditions as in vitro, mortality was higher in HeLa cells than in fibroblasts (non-malignant cells). Cytotoxicity was checked in both cell lines without the PTT mode; the nanohybrids do not seem to affect cell viability. These results make the nanohybrids very promising agents for NIR-PT and for targeting in cancer therapy, since non-malignant cells were not damaged.